Hierarchical CuO@ZnCo LDH heterostructured nanowire arrays toward enhanced water oxidation electrocatalysis. Issue 9 (26th February 2020) - Wang, Ting; Zhang, Xiaoxue; Zhu, Xiaojuan; Liu, Qian; Lu, Siyu; Asiri, Abdullah M.; Luo, Yonglan; Sun, Xuping
Abstract : As a durable electrocatalyst for water oxidation, a hierarchical heterostructured CuO@ZnCo layered double hydroxide nanowire array on a copper foil requires a low overpotential of 270 mV to attain 10 mA cm −2 in 1.0 M KOH. Abstract : It is of great importance to design and develop complex heterostructured nanocatalysts with superior electrochemical performance to that of single structured ones. Here, we report the hydrothermal fabrication of a hierarchical heterostructured CuO@ZnCo layered double hydroxide nanowire array on a copper foil (CuO@ZnCo LDH/CF). As a self-supported electrocatalyst for water oxidation, CuO@ZnCo LDH/CF has superior catalytic activity with the requirement of a low overpotential of 270 mV to attain 10 mA cm −2 in 1.0 M KOH. In addition, it shows strong durability to maintain its activity for at least 24 h.